Abdullah Qardash : IS Successor to Al-Baghdadi? - Mahzam, Remy (2019)
Abdullah Qardash, a former officer in Saddam Hussein’s army who rose through Islamic State’s ranks, was reported recently to be the successor to current leader, Abu Bakr al-Baghdadi. This is perhaps the first time a successor to the world’s most reclusive extremist leader has been mentioned. reflecting IS’ struggle to re-assert itself as a global movement.